JENIS MAKNA DALAM THE BOOK OF PROVERBS - CHASANDRA, LAHENGKO M. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled â€œTypes of Meaning in the Book of Proverbs.â€ The problems of this research focus on the seven types of meaning and their descriptions in the Book of Proverbs. The aims of the research are to identify, to classify the verses into the seven types of meanings, and to analyze the verses in the Book of Proverbs using Semantics approach. This research uses descriptive method. In collecting data, the writer focused on reading the words, phrases, or sentences in every verse from chapter 1-15 because the whole 7 types of meaning exist in chapter 1-15. The result of this research showed that there are conceptual meaning, connotative meaning, collocative meaning, reflective meaning, affective meaning, social meaning, and thematic meaning in the Book of Proverbs. The second result of this research is the seven types of meaning have variation in their descriptions. Â Keywords: Types, Meaning, Book of Proverbs